Feasibility of Crosslinked Acrylic Shape Memory Polymer for a Thrombectomy Device. (25th February 2014) - Muschenborn, Andrea D.; Hearon, Keith; Volk, Brent L.; Conway, Jordan W.; Maitland, Duncan J.
Abstract : Purpose . To evaluate the feasibility of utilizing a system of SMP acrylates for a thrombectomy device by determining an optimal crosslink density that provides both adequate recovery stress for blood clot removal and sufficient strain capacity to enable catheter delivery. Methods . Four thermoset acrylic copolymers containing benzyl methacrylate (BzMA) and bisphenol A ethoxylate diacrylate (Mn ∼ 512, BPA) were designed with differing thermomechanical properties. Finite element analysis (FEA) was performed to ensure that the materials were able to undergo the strains imposed by crimping, and fabricated devices were subjected to force-monitored crimping, constrained recovery, and bench-top thrombectomy. Results . Devices with 25 and 35 mole% BPA exhibited the highest recovery stress and the highest brittle response as they broke upon constrained recovery. On the contrary, the 15 mole% BPA devices endured all testing and their recovery stress (5 kPa) enabled successful bench-top thrombectomy in 2/3 times, compared to 0/3 for the devices with the lowest BPA content. Conclusion . While the 15 mole% BPA devices provided the best trade-off between device integrity and performance, other SMP systems that offer recovery stresses above 5 kPa without increasing brittleness to the point of causing device failure would be more suitable for this application.